The Communication Strategy of Ustadz Abdil Muhadir Ritonga in Spreading Islamic Da'wah Content on TikTok - Fadli, Andika; Madya, Efi Brata (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to examine the da’wah communication strategies employed by Ustadz Abdil Muhadir Ritonga through the social media platform TikTok in disseminating Islamic da’wah content. As a digital medium popular among younger generations, TikTok offers both significant opportunities and challenges for da’wah, particularly due to its short video duration and the dominance of entertainment-oriented content. A qualitative approach was applied using a case study method, with data collected through interviews, observations, and documentation.The findings reveal that Ustadz Abdil Muhadir Ritonga employs three da’wah communication strategies: sentimental (emotional), rational (intellectual), and sensory (practical). His distinctive style of da’wah is characterized by the use of humor, Islamic poetry, and a delivery that is heartfelt and easily understood by diverse audiences. These strategies have proven effective in capturing audience attention and fostering positive interaction on social media. This study underscores the importance of adapting da’wah strategies to technological developments and audience characteristics in the digital era.